The synthesis of graphene oxide covalently linked with nickel tetraamino phthalocyanine: A photoelectrochemical sensor for the analysis of rifampicin irradiated with blue light. Issue 10 (3rd July 2019) - Peng, Jinyun; Huang, Qing; Liu, Yuxia; Liu, Fengping; Zhang, Cuizhong; Huang, Yingying; Huang, Wei
Abstract : In this article, the fabrication and characterization of a photoelectrochemical (PEC) rifampicin sensor based on graphene oxide grafted with Ni tetraamino phthalocyanine was described, which presents an excellent PEC activity, sensitivity, and material stability. The synthesized graphene oxide grafted with Ni tetraamino phthalocyanine was characterized using ultraviolet–visible (UV–vis), Fourier transform infrared (FTIR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) analyses. Specifically, detection for rifampicin was based on the reduction of photocurrent caused by binding of the analyte to the sensing electrode surface. The fabricated sensor was characterized in a broad linear response range (0.025–71.3 μM) and with a low detection limit (2.5 nM), outperforming the previously reported sensors and thus being well suited for quality control and other applications, as confirmed by successful real‐life sample testing. Abstract : Nickel tetraamino phthalocyanine‐functionalized graphene oxide (NiTAPc‐GO) was prepared. NiTAPc‐GO was used to fabricate a highly selective and stable rifampicin photoelectrochemical (PEC) sensor. The fabricated sensor exhibited a wide linear response range and a low limit of detection. The developed sensor was used to detect rifampicin in real‐life samples.